The Link between Energy Economics, Consumer Behaviour and Tourism. A Literature Review - CHUCHU, Tinashe (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
Tourism globally is a rapidly advancing industry, and this has attracted much attention from practitioners and academics. However, the interrelatedness between energy economics, consumer behaviour and tourism are a fairly under-researched phenomenon. This research therefore serves as an attempt to investigate the link between the two and explore existing literature to provide new insights into how energy resources have impacted tourism growth and development. Select tourism destinations were utilised for purposes of this research. In order to collect enough and relevant data, a selection of empirical studies on tourism and energy economics from 2000 to 2019 were systematically reviewed, analysed and discussed. Publicly accessible government and industry data sources were utilised for purposes of the study as well as academic literature popular scientific databases that include Science direct, Ebsco and Emerald. Based on findings of the research recurring themes and trends were identified. Findings provided sufficient evidence to suggest that the success of the tourism industry is dependent on effective energy policies.